Epilepsy and inborn errors of metabolism in adults: The diagnostic odyssey of a young woman with medium‐chain acyl‐coenzyme A dehydrogenase deficiency. Issue 4 (17th August 2022) - Cani, Ilaria; Pondrelli, Federica; Licchetta, Laura; Minardi, Raffaella; Giangregorio, Tania; Mostacci, Barbara; Muccioli, Lorenzo; Di Vito, Lidia; Fetta, Anna; Barba, Carmen; Castioni, Carlo Alberto; Bordugo, Andrea; et al.
Abstract: We describe a case of epileptic encephalopathy in a young woman with undiagnosed medium‐chain acyl‐coenzyme A dehydrogenase deficiency (MCADD), who presented with an early‐onset focal motor status epilepticus (SE) then followed by permanent left hemiplegia and drug‐resistant epilepsy with neurodevelopmental delay. Throughout her clinical history, recurrent episodes of lethargy, feeding difficulties, and clustering seizures occurred, progressing into a super refractory SE and death at the age of 25 years. Although epilepsy is not a distinctive feature of MCADD, we advise considering this metabolic disease as a possible etiology of epileptic encephalopathy and hemiconvulsion‐hemiplegia‐epilepsy syndrome of unknown origin, on the chance to provide a timely and targeted treatment preventing development delay and evolution to SE. Adult patients with epilepsy of unknown etiology not screened at birth for inborn errors of metabolism, such as MCADD, should be promptly investigated for these treatable conditions.